Analytical profiling and antioxidant characterization of flavonoids from himalayan black soybean (Glycine max) - Pramod Kumbhar; Chandraprabhu Jangme; Mohini Salunke; Balaji Wakure (Journal of Applied Pharmaceutical Research, 2026)
Background: Black soybean is a leguminous crop of great phytochemical interest and importance in traditional systems due to its alleged health-promoting effects. To a great extent, these advantages are attributed to its flavonoid content, a class of polyphenols known for their strong antioxidant properties. This research was part of a significant task: conducting a comprehensive phytochemical characterization of the flavonoid profile in black soybean seeds and assessing their respective antioxidant potential in vitro. Methodology: Flavonoids were extracted from authentic seeds using 70% aqueous ethanol. UV-Vis, FTIR, and 1H NMR spectroscopy were used to elucidate the extract's functional groups and structure. Specific flavonoids (rutin, quercetin) were analyzed quantitatively by use of validated HPLC. In the determination of total flavonoid content, a spectrometric method was used. The DPPH radical-scavenging assay was used to determine antioxidant activity. Results and Discussion: Spectroscopic studies revealed the presence of typical flavone/flavonol skeletons. The HPLC quantification illustrated good method performance. The TFC was 5.91 mg QE/g extract. The extract exhibited high dose-dependent scavenging activity against the DPPH radical. High TFC was strongly correlated with antioxidant activity, confirming the bioactive capacity of black soybean, known for its flavanol-rich flavonoids. Conclusion: The results are scientifically confirmed: black soybean is rich in bioactive flavonoids with high antioxidant capacity and can therefore be used as a functional food ingredient or nutraceutical to treat oxidative stress.